Fingerprint pattern examination of right hand thumb in relation to Blood Group - Jha, L; Das, K D; Ahamad, Z (Janaki Medical College Journal of Medical Science, 2016)
Background and Objectives: The study of friction ridge patterns of fingertip is known as dermatoglyphics. Although human beings have been using fingerprints as a means of identification for a long time, in this study an effort has been made to study a fingerprint pattern examination of right hand thumb in relation to ABO Rh blood group, so that one can get an idea about the expected blood group from the study of fingerprint pattern and vice versa. Material and Methods: A plain thumb print was taken by applying ink to the tip of right hand thumb and place in the thumb directly on paper with a gen tle pressure and the rolled fingerprint was taken by rolling the thumb on paper from outward to inward in such a way as to obtain an impression of whole tip. The blood group was determined and recorded along with other details of the study subjects after taking inform consent. Data were entered in excel and analyzed. Results: It was observed that percentage of Loops were highest in AB blood group (76.92%) and O blood group with (71.05%) common in A and B blood group with 57.14%. Also, percentage of Whorls in A blood group was highest (42.86%) as compared to lowest in AB blood group (23.08%), in blood group B and O the distribution of whorls pattern are 39.28% and 28.95% respectively. Similarly, percentage of Arch was least in B blood group (3.84%). Conclusion: This study showed that there is an association between ridges of fingertip and different blood group. Janaki Medical College Journal of Medical Sciences (2015) Vol. 3 (2): 58-61